Penerapan Metode Latihan Passing Aktif untuk Meningkatkan Keterampilan Passing Pemain Futsal SMP Negeri 14 Lubuklinggau - Sorita, Asri Putra; Supriyadi, Muhammad; Syafutra, Wawan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to determine the improvement of basic passing skills through active passing training methods on the basic passing skills of futsal players at SMP Negeri 14 Lubuklinggau. This research uses an experimental method with a "one group pretest-posttest design". The population in this study were futsal players at SMP Negeri 14 Lubuklinggau, totaling 15 players. The instrument for measuring passing skills is the active passing test. The results of this research state that Ha is accepted and Ho is rejected based on the data results tcount 8.071 < and the final test data results are ttable 2.145 (tcount> ttable), which shows that active passing method training can improve the passing skills of futsal players at SMP Negeri 14 Lubuklinggau. Key words: active passing, passing, skill